PERPLEXITY EN EL PROCESO DE APRENDIZAJE DE LOS ESTUDIANTES DE LA CARRERA DE PEDAGOGÍA DE LAS CIENCIAS EXPERIMENTALES INFORMÁTICA, SECCIÓN MATUTINA DE LA UNIVERSIDAD TÉCNICA DE BABAHOYO, PERIODO ACADÉMICO ABRIL-AGOSTO 2024. - RENDÓN LIBERIO CRISTHEL YAMILETH (2024)
This research mentions how artificial intelligence is being implemented in educational institutions, so students are looking for new ways and methods to be able to achieve their learning more quickly and that is where perplexity as an artificial intelligence tool helps realization of new learning, which is why the objective of this research is to analyze the influence of perplexity on the learning process of students of the Pedagogy of Experimental Sciences Computer Science career, morning section, academic period April-August 2024. This Integration work has as applied methodology a mixed approach in which this research will be exploratory, descriptive and explanatory, depending on the research sources it will be documentary type which allowed information to be collected from reliable sources and finally this research work has a design not experimental. Thus, its population is 239 with a sample of 148 students. For the results, a questionnaire of 12 closed questions was carried out, which were favorable for this curricular research work since it could be shown that perplexity is an influence on the students' learning process since through this artificial intelligence the students, they are optimizing their learning. In addition, it was concluded that this perplexity artificial intelligence tool does favor the learning process.